Cash Holding, Leverage Dan Peluang Pertumbuhan Terhadap Keputusan Investasi Perusahaan - Supriyanto, Aldi (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2023)
Investment in property and real estate companies continued to decline in 2018 and 2019. The company's management is faced with investment decisions that can provide benefits for the company. The use of cash holding, leverage and growth opportunities in the company are considerations for the company's management in making more efficient investment decisions. This research aims to determine the influence of cash holding, leverage, and company growth opportunities on the company's investment decisions. This study uses a quantitative approach with a sample of 37 property and real estate companies on the Indonesia Stock Exchange. The results of the study stated that cash holding, leverage, and growth opportunities did not have a positive effect on investment decisions made by the company. Where cash holding, leverage, and growth opportunities only have an influence of 3.8% on the company's investment decisions, while 96.2% are influenced by other variables that are not studied.